Entrapment and retrieval of a diagnostic electrophysiological catheter in the Chiari network. Issue 6 (3rd September 2018) - Chu, Songyun; Solheim, Eivind; Chen, Jian; Hoff, Per Ivar; Schuster, Peter
Abstract: The Chiari networks are reticulated fibers of embryological remnant venous valves in the right atrium. In patients with this congenital variation, manipulation of diagnostic catheters can be difficult, and there is a substantial risk of entrapment during electrophysiological studies. We report a case of successful retraction of a diagnostic catheter entangled in the Chiari network with the use of a lead extraction tool during a scheduled atrial fibrillation ablation. Rescheduled cryoablation was performed without complication and provided a good outcome.